Revisiting E-Portfolio in Higher Education: English Language Education Students’ Point of View - Kurniawan, Dedy; Anastasia, Indri; Efriza, Dony; Rahmadani, Mutia (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This study aims to explore the implementation of portfolio in higher education, particularly in an English Language Education Department in Indonesia. Mixed method with concurrent combination was selected. Quantitative data were collected with a questionnaire (n = 74), while qualitative data were collected by three FGDs sessions (n= 21). The quantitative data were analyzed using descriptive statistics, while the qualitative data were analyzed thematically. These data were then interpreted simultaneously and four key themes were generated from the data: 1) Superficial understanding and skills in using portfolio, 2) Scarce and Partial Implementation of e-Portfolio, 3) Digital Technology as a Norm in Portfolio Implementation, and 4) Internalized Positive Views on Portfolio Implementation. These findings have shed light on the implementation of e-portfolio in this institution. Some recommendations were offered in order to improve its future implementation.